Are parents doing better when they are together? A study on the association between parental sensitivity and family-level processes. Issue 6 (2nd June 2016) - Udry-Jørgensen, Laura; Tissot, Hervé; Frascarolo, France; Despland, Jean-Nicolas; Favez, Nicolas
Abstract : The aim of this study was to evaluate the influence of one parent's presence on the quality of the interaction between the other parent and their three-month-old infant. Family interactions were observed in a sample of 69 two-parent families. Parental sensitivity was assessed during two sessions, first in a 'dyadic' context (D) and then in a 'dyad within the triad' context (DT). Subsequently, we compared maternal and paternal sensitivity in the D and DT contexts according to the quality of family functioning ('high coordination' versus 'low coordination'). The results showed that parents were significantly more sensitive in the DT context than in the D context. This effect appeared to vary according to the quality of family alliance. Moreover, family alliance was globally associated with sensitive parenting. This study helps clarify the role of the triad as a protective factor for early infant–parent dyads.